El teatro musical de Arena y Opinião: popular, histórico y auténticamente brasileño - Moreno, Iani (Latin American Theatre Review, 2016)
In the 1960s, a handful of Brazilian plays, presented as musicals, re-examined national historical figures. In these plays, the lines articulated by the actors carry as much weight as the musical notes and rhythms performed by the musicians. In Arena Conta Zumbi (1965), Arena Conta Tiradentes (1967), and Dr. Getúlio, Sua Vida e Sua Glória (1968), theatre troupes perform the life and historical times of prominent national heroes. The protagonists are characters whose lives are well known by all: King Zumbi of Palmares, Joaquim José da Silva Xavier, also known as Tiradentes, and former president Getúlio Vargas. The directors —Augusto Boal, Gianfrancesco Guarnieri, Alfredo Dias Gomes, and Antônio Ferreira Gullar— do not detract from the protagonists’ historical importance, but they do strip away superfluous details and information that have made these mythical figures appear saintly and virtuous and not the human beings that they were. Music creates a distance that allows the audience to better understand the implications of their actions and contributions to the national stage. These plays criticized the Brazilian military dictatorship of the time and had considerable influence on the Brazilian theatre of the future.